Corpo em palavras, movimento em histórias: trajetórias de formação docente em narrativas - Tavares, Gabriela Cruz (2024)
The dissertation "Body in Words, Movement in Stories: Trajectories of Teacher Training in Narratives" discusses teacher training narratives, using the autobiographical analysis of the subject Sensei, a Physical Education student. The study highlights the importance of the body as a symbol and vehicle of experiences, going beyond the physical vision, considering it as a reflection of the complexities of life and identity. The research, based on Paulo Freire's pedagogy, proposes a deep and reflective approach to teacher training. The title suggests that teacher training is not only academic, but a personal journey, represented by the "body in words" and "movement in stories". This implies that training experiences cannot be fully understood only through abstract theories, but are also lived and felt on a personal and physical level. The study focuses on the subject who symbolically receives the name of Sensei in our research, this is a 21-year-old student, from the Physical Education Degree course, from the Baturité Massif region. Our study explores autobiographical research, using the biographical method and interviews to narrate the trajectory of teachers. The research seeks to understand how autobiographical narratives reveal transgressive bodies in teacher training. By adopting a qualitative approach, the research recognizes the richness of human experiences, capturing nuances, motivations, and social interactions. The conclusion highlights the relevance of the analyses, especially under the influence of Paulo Freire, emphasizing the interconnection between teaching practice, academic experiences, and pedagogical principles. The research highlights the importance of the body in the construction of identity and values, recognizing the continuous need for an emancipatory and transformative education. In short, this dissertation provides a deep understanding of the complex journey of teachers towards professional development and the construction of their identity as educators, demonstrating that teacher training is a dynamic journey in constant evolution.